1‐Ethyl‐3‐Methyl‐Imidazolium Bis (Trifluoromethane‐ sulfonyl) Imide as an Electrolyte Additive in LiFePO4‐ Based Batteries for Suppressing Aluminum Corrosion. Issue 9 (11th September 2018) - Shangguan, Xuehui; Jia, Guofeng; Li, Faqiang; Liu, Suqin; Yang, Guowei; Wu, Kang; Wu, Zhijian
Abstract: Lithium bis (trifluoromethanesulfonyl) imide (LiTFSI) is a potentially useful electrolyte salt for use in Li‐ion batteries. LiTFSI, however, is associated with severe corrosion of Al current collectors. This study investigates the ionic liquid 1‐ethyl‐3‐methyl‐imidazolium bis (trifluoromethanesulfonyl) imide (EMITFSI) as an Al corrosion inhibitor in LiTFSI electrolytes. Different concentrations of EMITFSI are used as additives in 1 m LiTFSI‐based electrolytes to systematically assess the performance of lithium iron phosphate (LiFePO4 ) cathodes. The results from electron microscopy (SEM), X‐ray photoelectron spectroscopy (XPS), Cyclic voltammetry (CV) indicate that adding EMITFSI into LiTFSI‐based electrolytes can effectively prevent severe corrosion of Al caused by LiTFSI‐based electrolytes. The LiFePO4 cells that use 1 m LiTFSI+11 % EMITFSI‐based electrolytes demonstrate a superior rate capability and cycling stability when compared to cells that use the LiTFSI‐based electrolyte. Abstract : EMITFSI can protect the Al foil from corrosion and can stabilize Al foil in LiTFSI‐based electrolytes by forming an inactivation layer. SEM images of a fresh cathode and cathodes cycled with 1 M LiTFSI electrolyte or EMITFSI‐containing electrolyte. It is apparent that the fresh LiFePO4 surface is clean and smooth. For the cells after 10 cycles in 1 M LiTFSI and 11 wt% EMITFSI‐containing electrolytes, both of the LiFePO4 electrode surfaces are covered with film. In contrast, the film covering on the LiFePO4 cycled in 11 wt% EMITFSI‐containing electrolyte is compact and uniform, which confirms that the oxidative decomposition of EMITFSI efficiently suppresses the decomposition of the LiTFSI electrolyte.